2018
DOI: 10.3389/fendo.2018.00248
|View full text |Cite
|
Sign up to set email alerts
|

Metformin Use Is Not Associated With B12 Deficiency or Neuropathy in Patients With Type 2 Diabetes Mellitus in Qatar

Abstract: BackgroundMetformin may lead to B12 deficiency and neuropathy. There are no published data on the prevalence of Metformin-related B12 deficiency and neuropathy in the Arabian Gulf.AimsDetermine whether Metformin intake is associated with B12 deficiency and whether B12 deficiency is associated with diabetic peripheral neuropathy (DPN) and painful diabetic neuropathy.MethodsPatients with type 2 diabetes mellitus (T2DM) (n = 362) attending outpatient clinics at HMC underwent assessment of B12 levels, the DN4 ques… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
32
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 29 publications
(35 citation statements)
references
References 32 publications
3
32
0
Order By: Relevance
“…While most studies, including meta-analysis reviews, agree that there is an association between vitamin B12 deficiency and the intake of metformin in T2DM patients, a small number of studies have disputed this relationship. 4,5,15,16 The current study confirmed the association between a high metformin dose and vitamin B12 deficiency as concluded by previous studies. 3,10 Patients were found to be at a higher risk of developing vitamin B12 deficiency if they took a larger dose of metformin (>2000 mg/day) and for a longer duration (>4 years).…”
Section: Discussionsupporting
confidence: 91%
“…While most studies, including meta-analysis reviews, agree that there is an association between vitamin B12 deficiency and the intake of metformin in T2DM patients, a small number of studies have disputed this relationship. 4,5,15,16 The current study confirmed the association between a high metformin dose and vitamin B12 deficiency as concluded by previous studies. 3,10 Patients were found to be at a higher risk of developing vitamin B12 deficiency if they took a larger dose of metformin (>2000 mg/day) and for a longer duration (>4 years).…”
Section: Discussionsupporting
confidence: 91%
“…Concern has been raised regarding metformin‐associated vitamin B 12 deficiency and peripheral neuropathy; however, a recent meta‐analysis has shown that, whilst long‐term metformin use is associated with vitamin B 12 deficiency, it is not related to an increased prevalence of DPN . Furthermore, we have recently shown that the prevalence and severity of DPN and painful DPN were similar in people with and without B 12 deficiency .…”
Section: Treatment Of Diabetic Peripheral Neuropathymentioning
confidence: 85%
“…Some studies have also found that the administration of metformin is associated with deficiency of vitamin B 12 (VB12), whereas others have not detected such an association. Homocysteine, which is converted to methionine in the presence of VB12, is a marker for the activity of the vitamin.…”
Section: Introductionmentioning
confidence: 99%